Problems of translation of literary peculiarities in the story “Son of the Wolf”. (Eurasian Journal of Philology Science and Education, 2015)
The article compiled by N. Bekereshvili is entitled as “Problems in translation of literary peculiarities in the story “Son of the Wolf” written by Jack London ” refers to the comparative analysis of the fiction both in original and target language, made by N. Gal’ and E. Guroe; it also deals with the level of quality and adequacy. We pay special attention to epithets as the instruments of paysage creation. Paysage and symbolism are the basis of London’s literary method. That’s why the representation of these peculiarities in the translation is the main task of translator. In order to make the comparative analysis of the fiction we used synchronic and searching methods because both variants of translation were done in 60s of XX century. We also mention the fact of the small number of works, which is written about J. London literary method and its reconstruction in the translation into Russian. For this reason the topic of our research in this article is important today.
Keywords: realia; stylistic devices; equivalent; adequacy; symbol; paysage; semantics